2020
DOI: 10.1371/journal.pntd.0008549
|View full text |Cite
|
Sign up to set email alerts
|

Community-based sero-prevalence of chikungunya and yellow fever in the South Omo Valley of Southern Ethiopia

Abstract: Background Chikungunya (CHIK) and yellow fever (YF) are becoming major public health threats in East African countries including Ethiopia. In Ethiopia, there is no reliable information about the epidemiology of CHIK. This study aimed to assess a community-based sero-prevalence of CHIK and YF in the South Omo Valley, an endemic area for YF. Methods Between February and June 2018, blood samples were collected from study participants and screened for IgG antibody against CHIK virus (CHIKV) and YF virus (YFV) infe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
12
2

Year Published

2021
2021
2024
2024

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 15 publications
(14 citation statements)
references
References 41 publications
0
12
2
Order By: Relevance
“…The slightly higher seroprevalence that we found in the Gambella region could be explained by the higher rate of daily commuters from neighboring countries (South Sudan, Sudan), migration of refugees, and seasonal movement of pastoralists from North and West Africa in search of pasture. Our findings show a lower anti-YFV IgG antibody response compared to other seroprevalence studies conducted in South Omo, Ethiopia [22] where the authors found 49.5% seropositivity for YFV IgG antibodies. A higher seroprevalence of YFV IgG antibodies was also reported from the Borena area of Southern Ethiopia (12.5% of participants) [40], and Kenya (6% of participants) [41].…”
Section: Plos Onecontrasting
confidence: 82%
See 2 more Smart Citations
“…The slightly higher seroprevalence that we found in the Gambella region could be explained by the higher rate of daily commuters from neighboring countries (South Sudan, Sudan), migration of refugees, and seasonal movement of pastoralists from North and West Africa in search of pasture. Our findings show a lower anti-YFV IgG antibody response compared to other seroprevalence studies conducted in South Omo, Ethiopia [22] where the authors found 49.5% seropositivity for YFV IgG antibodies. A higher seroprevalence of YFV IgG antibodies was also reported from the Borena area of Southern Ethiopia (12.5% of participants) [40], and Kenya (6% of participants) [41].…”
Section: Plos Onecontrasting
confidence: 82%
“…Our study examines the community-based sero-epidemiology of YFV, CHIKV, and ZIKV in two selected districts of the Gambella region in South West Ethiopia. Previously a few studies on arboviruses have been conducted in other regions of Ethiopia and were mainly part of outbreak investigations at that time including dengue fever (DF) and YF [ 3 , 19 , 22 , 37 , 38 ].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…This observation may possibly reflect the now endemic nature of the disease, with more individuals becoming seropositive over time. As a matter of fact, the overall prevalence of seropositivity for CHIKV in our sample was numerically higher than that observed in the general healthy population in Reunion Islands (38.2%, 2005-6) [15], Ethiopia (43.6%, 2018) [16], and Zambia (36.9%, 2016) [17].…”
Section: Discussioncontrasting
confidence: 71%
“…However, the country has been hampered by challenges of lack of clinical experience to suspect and manage potential DF cases and by the absence of adequate laboratory diagnostic capabilities. As a result, DF cases possibly remain undiagnosed as mild or asymptomatic, misdiagnosed with other clinical manifestations resembling malaria, bacterial, or other viral infections or remaining unidentified febrile illness [13,23]. Therefore, DF cases, including epidemics, emerge and pose a significant unforeseen and none-responded challenge to the country due to weak health system, low experience of health service providers, and economic instability [24].…”
Section: Introductionmentioning
confidence: 99%